PENGARUH PEMBERIAN SUPLEMEN TERNAK ORGANIK SELARAS ALAM (STOSA) PADA BOBOT BADAN DAN KAMBING KACANG KONSUMSI PAKAN - , PRADITYA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Suplemen Ternak Organik Selaras Alam (STOSA) is a supplement for livestock that was created to increase body weight and reduce feed consumption. STOSA is an untested product thus research should be conducted to test that product. A research had been done to find out the effect of STOSA on body weight and feed consumption of kacang goat. Research was done using 12 kacang goats which were divided into 4 groups. Those groups were based on the mean distribution of kacang goatâs live weight and were sorted based on the dosage level of STOSA administration, those groups were A (control